Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the equation of the line in point-slope form using the given point [tex]\((-2, -6)\)[/tex], we follow several steps:
1. Identify points to use:
We will use the points [tex]\((-4, -11)\)[/tex] and [tex]\((-2, -6)\)[/tex] to calculate the slope [tex]\(m\)[/tex].
2. Calculate the slope [tex]\(m\)[/tex]:
The formula for the slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plug in the given points:
[tex]\[ m = \frac{-6 - (-11)}{-2 - (-4)} = \frac{-6 + 11}{-2 + 4} = \frac{5}{2} \][/tex]
3. Write the point-slope form:
The point-slope form of a linear equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Using the point [tex]\((-2, -6)\)[/tex] [tex]\((x_1, y_1)\)[/tex] and the calculated slope [tex]\(m = \frac{5}{2}\)[/tex]:
[tex]\[ y - (-6) = \frac{5}{2}(x - (-2)) \][/tex]
Simplify the expression:
[tex]\[ y + 6 = \frac{5}{2}(x + 2) \][/tex]
4. Compare with given options:
- [tex]\(y - 6 = \frac{5}{2}(x - 2)\)[/tex]
- [tex]\(y - 6 = \frac{2}{5}(x - 2)\)[/tex]
- [tex]\(y + 8 = \frac{2}{5}(x + 2)\)[/tex]
Clearly, [tex]\(y + 6 = \frac{5}{2}(x + 2)\)[/tex] matches our derived equation.
Thus, the correct equation is:
[tex]\[ y + 6 = \frac{5}{2}(x + 2) \][/tex]
1. Identify points to use:
We will use the points [tex]\((-4, -11)\)[/tex] and [tex]\((-2, -6)\)[/tex] to calculate the slope [tex]\(m\)[/tex].
2. Calculate the slope [tex]\(m\)[/tex]:
The formula for the slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plug in the given points:
[tex]\[ m = \frac{-6 - (-11)}{-2 - (-4)} = \frac{-6 + 11}{-2 + 4} = \frac{5}{2} \][/tex]
3. Write the point-slope form:
The point-slope form of a linear equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Using the point [tex]\((-2, -6)\)[/tex] [tex]\((x_1, y_1)\)[/tex] and the calculated slope [tex]\(m = \frac{5}{2}\)[/tex]:
[tex]\[ y - (-6) = \frac{5}{2}(x - (-2)) \][/tex]
Simplify the expression:
[tex]\[ y + 6 = \frac{5}{2}(x + 2) \][/tex]
4. Compare with given options:
- [tex]\(y - 6 = \frac{5}{2}(x - 2)\)[/tex]
- [tex]\(y - 6 = \frac{2}{5}(x - 2)\)[/tex]
- [tex]\(y + 8 = \frac{2}{5}(x + 2)\)[/tex]
Clearly, [tex]\(y + 6 = \frac{5}{2}(x + 2)\)[/tex] matches our derived equation.
Thus, the correct equation is:
[tex]\[ y + 6 = \frac{5}{2}(x + 2) \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.